2010
DOI: 10.1097/ncn.0b013e3181ec23fe
|View full text |Cite
|
Sign up to set email alerts
|

Stratifying Computer Literacy

Abstract: Institutions using a clinical information system which feeds an electronic medical record system must consider evaluation programs that measure the nurse's ability to use and understand the clinical data in the clinical information system. By measuring and tracking the nurse's level of computer literacy, training programs and system enhancements can be better designed. A well-designed system will lead to improved system acceptance and higher adoption rates. There is a need for a defined system implementation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…43,44 Therefore, NIC is considered a major determinant for successful clinical information systems, because nurses occupy the largest part of the healthcare workforce. For example, Turner 45 suggests that institutions adopting a clinical information system that feeds an electronic medical record system must consider evaluation programs that measure the nurse's ability to use and comprehend the clinical data in the clinical information system. In other words, nurses' achievements depend on whether they can make existing instruments work efficiently.…”
Section: The Elements Of Nurses' Informatics Competencies Assessment mentioning
confidence: 99%
“…43,44 Therefore, NIC is considered a major determinant for successful clinical information systems, because nurses occupy the largest part of the healthcare workforce. For example, Turner 45 suggests that institutions adopting a clinical information system that feeds an electronic medical record system must consider evaluation programs that measure the nurse's ability to use and comprehend the clinical data in the clinical information system. In other words, nurses' achievements depend on whether they can make existing instruments work efficiently.…”
Section: The Elements Of Nurses' Informatics Competencies Assessment mentioning
confidence: 99%
“…Because digital technology has become ubiquitous globally, other terms also emerged to describe the concept. For instance, computer skills (Ala‐Mutka, 2011; Indeed.com, 2022), computer literacy (Campbell & McDowell, 2011; Harper College, 2022; Turner, 2010), digital literacy (Belshaw, 2012), digital skills (Ecorys UK, 2016), informatics/information literacy (Bond & Procter, 2009; Cambridge Dictionary, 2022; Hwang & Park, 2011), E‐literacy (Klecun et al., 2014; Liou et al., 2015) and IT/ICT skills (Bunker, 2010; MacLure, 2014). The ever‐evolving range of digital capabilities subsumes all these definitions (Bartlett‐Bragg, 2017) and more since then.…”
Section: Introductionmentioning
confidence: 99%
“…Kunz also wrote about the potential disadvantages of the EMR, including varying levels of computer proficiency. An article by Turner (2010) discussed evaluation programs that measure nurses' ability to comprehend and understand the new EMR. The research showed that these programs encourage optimistic perceptions of the new electronic systems and in return promote adaption.…”
mentioning
confidence: 99%